DETERMINAN INTERNET FINANCIAL REPORTING (IFR) DI BURSA EFEK INDONESIA - Muhammad Demiyan, - (2019)
This researcher aims to determine the effect of Company Size, Age of Listing and Public Ownership of Shares on Internet Financial Reporting (IFR). The sampling technique uses the Purpose sampling method. The sample in this study is a company that is included in the calculation of LQ-45 from 2015 to 2017. Samples were taken by means of purposive sampling method, so that an adequate sample obtained for this study was 35 LQ-45 companies. The analysis technique uses multiple regression analysis with SMART PLS 3.0. The results of hypothesis testing found that the size of the company had a significant effect on Internet Financial Reporting (IFR). Age listing and public ownership of shares have no significant effect on Internet Financial Reporting (IFR).